Vitamin D status and muscle injury risk in elite male football players over 3 seasons - Arce, J.; Viar, T.; Lekue, J. A.; Angulo, P.; Martin-Garetxana, I.; Bikandi, E.; Monasterio, X.; Larruskain, J. (British Journal of Sports Medicine, 2021)
Background: Vitamin D has a role in skeletal muscle function and metabolism, however, its influence on muscle injury risk remains unclear. Objective: To evaluate the association between Vitamin D status and muscle injury risk. Design Prospective cohort study. Setting Elite male football team from Spanish LaLiga. Participants: 41 players were prospectively followed from 2016-2017 to 2018-2019. Assessment of Risk Factors Injuries and exposure time were recorded by the team doctor following the FIFA consensus. Blood analyses were performed in 4 different season periods (July, October, January and May). Main Outcome Measurements: Serum 25-hydroxyvitamin D levels were compared between periods using Student's T-test. The association of Vitamin D with 56 muscle injuries requiring 4 or more days of absence was investigated using a Coxfrailty model. The influence of days of absence due to all injuries on between-period changes in Vitamin D was assessed using linear mixed models. Results: Vitamin D levels were highest in July (mean±SD; 48.1 ±9.9 ng/ml, p<0.001 vs. other periods), and lowest in January (27.3±7.9 ng/ml, p<0.001). There were no differences between October (37.3±8.3 ng/ml) and May (34.5±10.7 ng/ ml, p=0.89). There was no association between continuous Vitamin D levels and muscle injuries adjusting for season period [hazard ratio=1.01, 95% confidence interval (CI) =0.97-1.05, p=0.66]. Players in the lowest period-specific quartile, i.e. with the lowest vitamin D levels, had a 2.29 times lower risk of injury (95% CI=0.97-5.41, p=0.06, 1.30 muscle injuries/1000 h) compared with players in the middle (3.24/1000 h) and highest (2.87/1000 h) quartiles combined. Days of absence were negatively associated with changes in Vitamin D levels after adjusting for season period (B=-0.06, 95% CI=-0.13-0.01, p=0.06). Conclusions: The association of Vitamin D status with muscle injuries should be further explored as studies are contradictory. Seasonal variations and being injured should be considered when supplementing with Vitamin D.